The impact of Climate Change on extreme winds over northern Europe according to CMIP6 - Larsén, Xiaoli Guo; Imberger, Marc; Hannesdóttir, Ásta (Frontiers in Energy Research, 2024)
We study the possible effect of climate change on the extreme wind over northern Europe using data from 18 models of the Sixth Phase of the Coupled Model Intercomparison Project (CMIP6) and the high-emission Shared Socioeconomic Pathway 5-8.5 (SSP585) scenario. We use the spectral correction method to correct the 6-hourly wind speeds and calculate the 50-year wind at an equivalent temporal resolution of 10 minutes, consistent with the International Electrotechnical Commission (IEC) standard. We obtain the possible effect of climate change through the comparison of the extreme wind parameters, including the 50-year wind and the 95%-percentile of the wind speed, and the change in turbine class at 50 m, 100 m and 200 m, between a near future period (2020–2049) and the historic period (1980–2009). The analysis shows an overall increase in the extreme winds in the North Sea and the southern Baltic Sea, but a decrease over the Scandinavian Peninsula and most of the Baltic Sea. However, the suggested change is not significant enough to conclude whether higher or lower classes of turbines will be needed in this area in the future.